Safety in Numbers: Progressive Implementation of a Robotics Program in an Academic Surgical Oncology Practice. (August 2016) - King, Jonathan C.; Zeh, Herbert J.; Zureikat, Amer H.; Celebrezze, James; Holtzman, Matthew P.; Stang, Michael L.; Tsung, Allan; Bartlett, David L.; Hogg, Melissa E.
Background . Robotic-assisted surgery has potential benefits over laparoscopy yet little has been published on the integration of this platform into complex surgical oncology. We describe the outcomes associated with integration of robotics into a large surgical oncology program, focusing on metrics of safety and efficiency. Methods . A retrospective review of a prospectively maintained database of robotic procedures from July 2009 to October 2014 identifying trends in volume, operative time, complications, conversion to open, and 90-day mortality. Results . Fourteen surgeons performed 1236 cases during the study period: thyroid (246), pancreas/duodenum (458), liver (157), stomach (56), colorectal (129), adrenal (38), cholecystectomy (102), and other (48). There were 38 conversions to open (3.1%), 230 complications (18.6%), and 13 mortalities (1.1%). From 2009 to 2014, operative volume increased (7 cases/month vs 24 cases/month; P < .001) and procedure time decreased (471 ± 166 vs 211 ± 140 minutes; P < .001) with statistically significant decreases for all years except 2014 when volume and time plateaued. Conversion to open decreased (12.1% vs 1.7%; P = .009) and complications decreased (48.5% vs 12.3%; P < .001) despite increasing complexity of cases performed. There were 13 deaths within 90 days (5/13 30-day mortality) and 2 (15.4%) were from palliative surgeries. Conclusions . Implementation of a diverse robotic surgical oncology program utilizing multiple surgeons is safe and feasible. As operative volume increased, operative time, complications, and conversions to open decreased and plateaued at approximately 3 years. No unanticipated adverse events attributable to the introduction of this platform were observed.